2015
DOI: 10.1186/s40539-015-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electron distribution on efficiency droop for GaN-based light emitting diodes

Abstract: By modulating the indium composition in the quantum barriers of InGaN-based LEDs, the influence of electron distribution, electron overflow and Auger recombination on the external quantum efficiency (EQE) and droop effect have been investigated. Experimental results as well as numerical simulations reveal that the electron distribution is the key factor to influence both the peak efficiency and droop effect. The results show that the high electron concentration in the individual quantum well can stimulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Increasing bias voltage further is seen as efficiency roll‐off and device breakdown. The exact reason for efficiency roll‐off is beyond the scope of this paper; however, we speculate that it is due to nonradiative carrier loss mechanism at higher injection levels . We have also fabricated the device without PEIE and MoO 3 , but efficiency numbers are found to be much lower—it might be due to poor injection properties and morphological issues (see in Table S3 and Figures S5–S7, Supporting Information).…”
Section: Resultssupporting
confidence: 90%
“…Increasing bias voltage further is seen as efficiency roll‐off and device breakdown. The exact reason for efficiency roll‐off is beyond the scope of this paper; however, we speculate that it is due to nonradiative carrier loss mechanism at higher injection levels . We have also fabricated the device without PEIE and MoO 3 , but efficiency numbers are found to be much lower—it might be due to poor injection properties and morphological issues (see in Table S3 and Figures S5–S7, Supporting Information).…”
Section: Resultssupporting
confidence: 90%
“…The light emissions are located at 455 nm, and except for the decreased intensity, there is no change in the peak wavelength. This indicates that there is no difference of the indium concentration in the multiple quantum wells 21 during the operation. Figure 3 shows the forward voltage at 350 mA for each sample measured at different stress intervals.…”
Section: Methodsmentioning
confidence: 91%
“…In addition, some researchers have studied the carrier distribution in the active region and its influence on the efficiency droop, and reported that the carrier distribution is a key factor affecting both the peak efficiency and efficiency droop. [8] To obtain high-efficiency GaN-based LEDs, many works have been carried out in optimizing GaN-based LEDs structures, and the use of AlGaN layers in GaN-based LEDs structures is a practical design method. Lin et al [9] reported that the inserted AlGaN layer between the n-type GaN layer and the InGaN active region can obtain higher peak efficiency and reduce efficiency droop at higher injection level.…”
Section: Introductionmentioning
confidence: 99%